EFEKTIFITAS PROGRAM KELUARGA BERENCANA KONTAP PRIA KECAMATAN KASIMAN KABUPATEN BOJONEGORO - jurnalmap map; Heni Indarti; Hadi Susanto; Arini Sulistyowati (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
The purpose of this study was to describe the effectiveness of male contraception family planning programs, supporting and inhibiting factors in Kasiman District, Bojonegoro Regency. This type of research is a qualitative descriptive study. Data collection techniques by observation, interview and documentation. Processing and data analysis using descriptive analysis. The results showed that the Men's Contraception Family Planning Program in Kasiman District, Bojonegoro Regency had been implemented and was quite effective in suppressing the population growth rate. The socialization of the Men's Contraception Family Planning Program has been done well and is quite effective, the socialization media used to introduce the Men's Contraception KB Program uses posters and leaflets as well as cooperation with other parties. The obstacle in the implementation of the Men's Contraception KB Program is people's understanding that the Men's Contraception Family Planning Program can affect sexual relations with their partners.Keywords: effectiveness, family planning, male conting.